Deletion of the murine ortholog of human 9p21.3 locus promotes atherosclerosis by increasing macrophage proinflammatory activity - Kettunen, Sanna; Ruotsalainen, Anna-Kaisa; Örd, Tiit; Suoranta, Tuisku; Heikkilä, Janne; Kaikkonen, Minna U.; Laham-Karam, Nihay; Ylä-Herttuala, Seppo (Frontiers in Cardiovascular Medicine, 2023)
Several GWAS have reported a risk locus for Coronary Artery Disease (CAD) in the 9p21.3 chromosomal region. A lncRNA in the INK4 locus (ANRIL) is encoded from this area and its genetic variance has a strong association with CAD, but its mechanisms in atherogenesis have remained unclear. The present study aimed to investigate the role of murine ortholog of human 9p21.3 locus in atherogenesis in hypercholesterolemic mice. Murine 9p21.3 ortholog knockout mice (Chr4Δ70kb/Δ70kb) were crossbred with Ldlr-/-ApoB100/100 mice and atherosclerotic plaque size and morphology were analyzed on a standard or a high fat diet (HFD). Hematopoietic cell specific effect of Chr4Δ70kb/Δ70kb on atherosclerotic plaque development was studied via bone marrow (BM) transplantation, where Chr4Δ70kb/Δ70kb or wild-type BM was transplanted into Ldlr-/-ApoB100/100 mice. The role of Chr4Δ70kb/Δ70kb in macrophage M1/M2 polarization was studied. In addition, single-cell sequencing data from human and mouse atheroma were analyzed to show the expression profiles of ANRIL and its murine equivalent Ak148321 in the plaques. Both systemic and hematopoietic Chr4Δ70kb/Δ70kb increased atherosclerosis in Ldlr-/-ApoB100/100 mice after 12 weeks of HFD. The systemic Chr4Δ70kb/Δ70kb also elevated the circulating leukocyte number. Chr4Δ70kb/Δ70kb BMDMs showed an enhanced M1 polarization in vitro. Single-cell sequencing data from human and mouse atheroma revealed ANRIL and Ak148321 being mainly expressed in immune cells. These data demonstrate that both systemic and bone marrow specific deletion of murine 9p21.3 risk locus ortholog promotes atherosclerosis and regulates macrophage pro-inflammatory activity, suggesting the inflammation driven mechanisms of the risk locus on atherogenesis.